2016
DOI: 10.1095/biolreprod.116.143412
|View full text |Cite
|
Sign up to set email alerts
|

SMAD3 Activation: A Converging Point of Dysregulated TGF-Beta Superfamily Signaling and Genetic Aberrations in Granulosa Cell Tumor Development?

Abstract: Ovarian granulosa cell tumors (GCTs) are rare gynecologic tumors in women. Due to the rarity and limited research efforts invested, the etiology of GCTs remains poorly defined. A landmark study has discovered the mutation of forkhead box L2 (FOXL2) as a genetic hallmark of adult GCTs in the human. However, our understanding of the role of cell signaling in GCT development is far from complete. Increasing lines of evidence highlight the importance of TGF-beta (TGFB) superfamily signaling in the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 90 publications
1
18
0
Order By: Relevance
“…These ligands bind to their membrane receptors and trigger the serine/threonine protein kinase activity of type 2 receptor (TGFBR2) and type 1 receptor (TGFBR1), and then the activated receptor phosphorylates intracellular SMAD2 (Sma- and Mad-related protein 2) and SMAD3. Subsequently, phosphorylated SMAD2 and SMAD3 form a heteromeric complex with SMAD4 (co-SMAD, the central signaling component of the TGF-β superfamily) 27,28 . Ultimately, the complex translocates into the nucleus and regulates gene expression by binding to the target gene promoter region, termed an SMAD-binding element (SBE), and recruiting distinct transcription factors 29 .…”
Section: Introductionmentioning
confidence: 99%
“…These ligands bind to their membrane receptors and trigger the serine/threonine protein kinase activity of type 2 receptor (TGFBR2) and type 1 receptor (TGFBR1), and then the activated receptor phosphorylates intracellular SMAD2 (Sma- and Mad-related protein 2) and SMAD3. Subsequently, phosphorylated SMAD2 and SMAD3 form a heteromeric complex with SMAD4 (co-SMAD, the central signaling component of the TGF-β superfamily) 27,28 . Ultimately, the complex translocates into the nucleus and regulates gene expression by binding to the target gene promoter region, termed an SMAD-binding element (SBE), and recruiting distinct transcription factors 29 .…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have revealed that histone lysine demethylases such as KDM3A play important roles in renal cell carcinoma, the most common kidney cancer, via hypoxia-mediated angiogenesis pathways ( 77–79 ). Smad3 is an intracellular signal transducer and transcriptional modulator activated by transforming growth factor (TGF)-β ( 80 ). On the molecular level, TGF-β/Smad3 signaling pathway plays a central role in fibrotic kidney disease ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…A causal link between the mRNA expression levels of TGFBR1 and the development of GCTs in humans has not been established [ 43 ]. Growing evidence supports that activation of TGFB/activin signaling may represent a driving force of GCT development in mice [ 44 ]. It has also been found that TGFB/activin signaling is active in human GCTs [ 32 , 45 ].…”
Section: Discussionmentioning
confidence: 99%